Konsep Sombong Dalam Al-Quran Berdasarkan Metode Pendekatan Tematik Digital Quran - Parlina, Ika; Hidayat, Tatang; Istianah, Istianah (Civilization Research: Journal of Islamic Studies, 2022)
Islam is a religion that teaches people to be noble and noble. The Prophet Muhammad Shallallahu ‘Alaihi Wa Sallam was the most perfect human being. Allah Subhanahu Wata'ala in the Al-Quran and as-Sunnah commands us to have noble morals and avoid despicable morals. The purpose of this study is to analyze the concept of arrogance in the Quran based on the digital Quran thematic approach method. This research uses a qualitative approach and the method of digital Quran thematic approach. Based on the results of the study, one of the despicable morals that every Muslim should avoid is arrogance. Arrogance is seeing oneself as above the truth and feeling more than others. An arrogant person feels himself perfect and sees himself as above others. The verses of the Qur'an mention a lot about the nature of arrogance itself. Through the digital thematic approach of the Quran, there are 28 verses of the Quran that mention the term arrogance.